Analysis of the effectiveness of VPN and PPTP Protocol in E-Link Health Report Application Using NDLC Method - Amadi, Dwi Nor; Budiman, Arief; Utomo, Pradityo (Journal of Information System and Informatics, 2024)
The rapid development of computer networks and data communications has significantly impacted all government sectors in Indonesia. The Madiun Regency Health Service relies on a web-based health reporting application, E-link Health Report, to manage health information data from community health centers. However, this application is vulnerable to cyber-attacks, necessitating enhanced security measures. To address this issue, the health service implemented a Virtual Private Network (VPN) using the Point-to-Point Tunneling Protocol (PPTP) to bolster system security. The aim of this research is to analyze the effectiveness of the implemented VPN with PPTP protocol in enhancing network reliability and data transmission security. The Network Development Lifecycle (NDLC) method was employed to conduct this analysis, focusing on parameters such as network reliability and the ability to secure data transmission against cyber threats. The results demonstrate a significant improvement in both network reliability and data transmission security following the implementation of the VPN with PPTP protocol. This study provides a comprehensive comparison of network performance before and after the implementation, highlighting the effectiveness of VPNs in securing web-based health reporting applications.